2002
DOI: 10.1002/jso.10063
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and its correlation with proliferative activity in rectal cancer

Abstract: Our results suggest that the susceptibility to apoptosis in rectal cancer is clearly related to the proliferative activity and high turnover rate of tumor cells may contribute to lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In fact, both Watanabe et al [28] and Evertsson et al [29] observed an increase in apoptosis and proliferation activities during the course of tumour progression from early to advanced stages of CRC. The same conclusion was reached in a study of rectal cancer by Kim et al [30]; these researchers also linked apoptosis to lymphatic invasion. Recently, authors that were investigating the relationship between KRAS mutations and prognoses for CRC cases have observed that KRAS mutations lead to the higher turnover of colorectal tumour cells, which stimulates both mitosis and apoptosis and is related to a poor survival of CRC [31].…”
Section: Discussionsupporting
confidence: 73%
“…In fact, both Watanabe et al [28] and Evertsson et al [29] observed an increase in apoptosis and proliferation activities during the course of tumour progression from early to advanced stages of CRC. The same conclusion was reached in a study of rectal cancer by Kim et al [30]; these researchers also linked apoptosis to lymphatic invasion. Recently, authors that were investigating the relationship between KRAS mutations and prognoses for CRC cases have observed that KRAS mutations lead to the higher turnover of colorectal tumour cells, which stimulates both mitosis and apoptosis and is related to a poor survival of CRC [31].…”
Section: Discussionsupporting
confidence: 73%
“…We observed that patients showing both high apoptosis and high proliferation, of which 68 % of the patients corresponded to the “all low” combined marker group, showed the shortest survival. This finding is supported by literature, in which both increased apoptosis and increased proliferation were reported in rectal tumors with lymph node metastases as compared to non-metastatic tumors [50]. The distorted balance between the apoptosis pathways and cellular proliferation in the “all low” combined marker group hence might explain the observed survival data.…”
Section: Discussionsupporting
confidence: 83%
“…The interobserver agreement of percentage scores may be better assessed in colorectal adenomas known to frequently overexpress the protein. 23 Our results show that Bcl-2 expression scored as 0% positive tumor cells vs any tumor cell staining leads to the highest degree of interobserver agreement in rectal tumors of the same stage.…”
Section: Discussionmentioning
confidence: 56%
“…This result is in line with the literature which states that the frequency of Bcl-2 expression in rectal carcinoma is less than 30%. 23 Kim et al 23 demonstrated that the rate of Bcl-2 overexpression decreases with more advanced Dukes stage. In this study, 98% of rectal biopsies were taken from patients with clinically diagnosed cT3 tumors.…”
Section: Discussionmentioning
confidence: 99%